2020
DOI: 10.1186/s12885-020-07497-7
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume and platelet distribution width serve as prognostic biomarkers in skull base chordoma: a retrospective study

Abstract: Background Increasing studies have demonstrated that activated platelets play an essential role in tumour progression. However, the level and prognostic role of platelet indices in chordoma patients remain unclear. The aim of the current study was to characterize the prognostic performance of platelet count (PLT), mean platelet volume (MPV) and platelet distribution width (PDW) in skull base chordoma patients. Methods 187 primary sku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Although our study failed to show the prognostic value of MPV, the PDW was another novel biomarker in predicting prognosis for RCC patients, which has not been investigated before. Several studies have shown high PDW was associated with poor survival in hepatocellular, breast cancers as well as skull base chordoma [31][32][33]. However, low PDW has also been reported that correlated with worse survival in endometrial, esophageal, gastric cancers [34][35][36], which consistent with our study result that low PDW was related to shorter PFS in RCC patients.…”
Section: Discussionsupporting
confidence: 91%
“…Although our study failed to show the prognostic value of MPV, the PDW was another novel biomarker in predicting prognosis for RCC patients, which has not been investigated before. Several studies have shown high PDW was associated with poor survival in hepatocellular, breast cancers as well as skull base chordoma [31][32][33]. However, low PDW has also been reported that correlated with worse survival in endometrial, esophageal, gastric cancers [34][35][36], which consistent with our study result that low PDW was related to shorter PFS in RCC patients.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, 187 skull base chordoma patients (98 males and 89 females) with a mean age of 40.1 (SD, 15.3) years were included in current retrospective research. 22 Of these patients, 126 (67.4%) patients had the classical pathological type of chordoma, and the remaining 61 (32.6%) patients got chondroid chordoma, no dedifferentiated chordoma was observed. 4 There were 57 (30.5%) patients with soft tumors and 130 (69.5%) patients who harbored moderate or tough tumors.…”
Section: Resultsmentioning
confidence: 98%
“…Finally, 187 patients with primary skull base chordoma were enrolled, and this cohort has been detailed in our previous study. 22 …”
Section: Methodsmentioning
confidence: 99%
“…The clinical information (age, classified by 55 years; gender; tumour volume, classified by 20 cm 3 ; blood supply, abundant (tumour resection surface with a tendency to bleed and is hard to aspirate clearly), poor (limited bleeding that is easy to aspirate clearly) and moderate (between poor and abundant); texture, classified as hard (tumours could hardly be excised without scissor or punch forceps), soft (tumours could be easily suctioned when using the aspirator) and moderate (between hard and soft); etc.) of the 84 patients was reviewed as our previous study reported and is detailed in Table 4,29,30 . IHC was performed using the Leica Bond III automated system as we have described previously 2 .…”
Section: Methodsmentioning
confidence: 99%
“…of the 84 patients was reviewed as our previous study reported and is detailed in Table S4 . 4 , 29 , 30 IHC was performed using the Leica Bond III automated system as we have described previously. 2 Primary antibody against ATG5 (sc‐133158, 1:50; Santa Cruz Biotechnology) was used for IHC of chordoma specimens.…”
Section: Methodsmentioning
confidence: 99%